Demographic and parasitic infection status of schoolchildren and sanitary conditions of schools in Sanliurfa, Turkey - Seyrek Adnan; Ulukanligil Mustafa (BMC, 2003)
Abstract Background The design and development of school health programmes will require information at demographic characteristics of schoolchildren and the major health burdens of the school-age group, the opportunities for intervention and the appropriateness of the available infrastructure. This study aims to analyse demographic and parasitic infections status of schoolchildren and sanitary conditions of schools in Sanliurfa province of south-eastern Turkey. Method Three primary schools were randomly selected in the shantytown, apartment and rural districts. A total of 1820 schoolchildren between 7-14 years age were took part to the survey of whom 1120 (61.5%) were boys and 700 (38.4%) were girls. A child form (including child's name, sex, age, school grade and parasitic infections) and school survey form (including condition of water supply, condition of latrines, presence of soaps on the basins and presence of garbage piles around to the schools) were used for demographic, parasitic and sanitary surveys. Stool samples were examined by cellophane thick smear technique for the eggs of intestinal helminths. Results The demographic survey showed that number of schoolchildren was gradually decreased as their age's increase in shantytown school. The sex ratio was proportional until the second grade, after which the number of females gradually decreased in children in shantytown and rural schools while, in apartment area, schoolchildren was proportionally distributed between age groups and gender even the high-grade students. The prevalence of helminthic infections was %77.1 of the schoolchildren in shantytown, 53.2% in apartment district and 53.1% of rural area. Ascaris lumbricoides was the most prevalent species and followed by Trichuris trichiura, Hymenolepis nana and Taenia species in three schools. Sanitation survey indicated that the tap water was limited in shantytown school, toilet's sanitation was poor, available no soaps on lavatories and garbage piles were accumulated around the schools in shantytown and rural area, while, the school in apartment area was well sanitised. Conclusions These results indicated that burden of parasitic infections and poor sanitation conditions constituted public health importance among to the shantytown schoolchildren. School health programmes including deworming and sanitation activities through the health education and improvement of sanitation conditions in the schools have a potential to better health and education for schoolchildren. These programmes also offer the potential to reach significant numbers of population in the shantytown schools with high level of absenteeism.